Alternative Culture Center Space N.O.: arena order all trials (Palíndromo, 2024)
This article deals with issues related to art history specifically the time of contemporary art in Brazil and especially the Culture Alternative Center NO (Space NO), that despite the short time of existence of space marked the cultural art scene of Porto Alegre between the late 1970s and early 1980s Formed by local artists as well as present their conceptual art productions made possible the coming of the great artists of the center of the country. Space NO was relevant for designing local artists at national and international level.
Keywords: alternative space; contemporary art; conceptual art